Review of the literature related to audit quality and integrated reporting quality in Jordanian companies - Jarah, Baker Akram Falah; Alshehadeh, Abdul Razzak; Al-Zaqeba, Murad Ali Ahmad; Al-Bataineh, Fuad A.; Al-khawaja, Haneen A. (Edelweiss Applied Science and Technology, 2024)
Audit quality is a key element in improving transparency and credibility in integrated reporting. Integrated reporting is of great interest to audit firms and their stakeholders worldwide. This interest stems from the key role auditors play in enhancing corporate reporting. Therefore, this study aims to fill the gap in the literature by investigating the role of audit quality and integrated reporting quality in Jordanian companies. As a result, companies bear increasing responsibility when preparing integrated reports and must undergo rigorous auditing to detect errors and fraud. Therefore, companies in Jordan rely heavily on audit quality through factors related to auditors’ independence, professional experience, and adherence to international auditing standards. Good auditing enhances the effectiveness of corporate governance, which positively impacts financial stability and companies’ reputation in the market. Therefore, companies that adopt these reports achieve better performance in the market, increase customer loyalty, and improve their reputation in the global regulatory environment.